1994
DOI: 10.1002/jor.1100120113
|View full text |Cite
|
Sign up to set email alerts
|

Aging, vertebral density, and disc degeneration alter the tensile stress‐strain characteristics of the human anterior longitudinal ligament

Abstract: The mechanical properties of the human lumbar anterior longitudinal ligament were investigated, and the influence of aging, disc degeneration, and vertebral bone density on these properties was determined. Tensile mechanical properties of the vertebra-anterior longitudinal ligament-vertebra complex were determined for 16 segments from cadavera of individuals who had been 21-79 years old (mean, 52.1 years) at the time of death. Regional strain patterns associated with three sites across the width and three site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 28 publications
(44 reference statements)
0
16
0
Order By: Relevance
“…14 -16 Biomechanical studies on the failure in human lumbar spinal ligaments are also rare. [17][18][19] To model failure of ligaments in an impact, ranging from falls to automobile crashes or aircraft ejections, it is imperative to obtain information about the deformation and failure responses of the ligaments at comparable fast strain rates.To the authors' knowledge, only one published study examines rate-sensitive failure properties of cervical spinal ligaments (anterior longitudinal ligament and ligamentum flavum) at deformation rates ranging from 8.89 to 2500 mm/s. 20 There are several gaps in the existing study.…”
mentioning
confidence: 99%
“…14 -16 Biomechanical studies on the failure in human lumbar spinal ligaments are also rare. [17][18][19] To model failure of ligaments in an impact, ranging from falls to automobile crashes or aircraft ejections, it is imperative to obtain information about the deformation and failure responses of the ligaments at comparable fast strain rates.To the authors' knowledge, only one published study examines rate-sensitive failure properties of cervical spinal ligaments (anterior longitudinal ligament and ligamentum flavum) at deformation rates ranging from 8.89 to 2500 mm/s. 20 There are several gaps in the existing study.…”
mentioning
confidence: 99%
“…In our study, an age-related decrease in the failure load, failure elongation, and stiffness was observed for all three ligaments. To the authors' knowledge, there are only data for the lumbar ALL in the study by Neumann [29], that analyzed the age effect and showed the same tendency of the failure load and failure stress decreasing with age. The age effect has been reported for the LF [30], and our study showed only a 2-time decrease in the LF failure properties, as compared to a 4-time decrease in this study.…”
Section: Discussionmentioning
confidence: 77%
“…In a few studies, age related changes of isolated spine ligaments have been analyzed (lumbar ALL [29] and LF [30]). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tensile mechanics of the adult spine has been evaluated in a number of studies (Panjabi et al, 1978;Cusick et al, 1982;Myklebust et al, 1988;Neumann et al, 1994;Myers and Winkelstein, 1995;Yoganandan et al, 1996), but only sparsely investigated in the immature populace. Miller and Skogland (1982) found that the adolescent spine is 1-10 times more flexible than the adult spine depending upon the applied load.…”
Section: Introductionmentioning
confidence: 99%